Axial tubule junctions activate atrial Ca2+ release across species - Brandenburg, Sören; Schmidt, Constanze; Wiedmann, Felix Tobias (Frontiers in physiology, 2018)
Rationale: Recently, abundant axial tubule (AT) membrane structures were identified deep inside atrial myocytes (AMs). Upon excitation, ATs rapidly activate intracellular Ca2+ release and sarcomeric contraction through extensive AT junctions, a cell-specific atrial mechanism. While AT junctions with the sarcoplasmic reticulum contain unusually large clusters of ryanodine receptor 2 (RyR2) Ca2+ release channels in mouse AMs, it remains unclear if similar protein networks and membrane structures exist throughout species, particularly those relevant for atrial disease modeling. Objective: To examine and quantitatively analyze the architecture of AT membrane structures and associated Ca2+ signaling proteins across species from mouse to human. Methods and Results: We developed superresolution microscopy (nanoscopy) strategies for intact live AMs based on a new custom-made photostable cholesterol marker and immunofluorescence imaging of Ca2+ channel clusters in fixed tissue sections from human and rodent atria. Consistently, in mouse, rat, and rabbit AMs, intact cell-wide tubule networks continuous with the surface membrane were observed mainly composed of ATs. Moreover, co-immunofluorescence nanoscopy showed large L-type Ca2+ channel clusters adjacent to extensive junctional RyR2 clusters at ATs. However, only junctional RyR2 clusters were highly phosphorylated and may thus prime Ca2+ release at ATs for rapid signal transduction. While the density of the L-type Ca2+ current was similar in human and mouse AMs, the amplitude and kinetics of the Ca2+ transient showed quantitative differences. Importantly, local intracellular Ca2+ release from AT junctions occurred through instantaneous action potential propagation through transverse tubules (TTs) from the surface membrane. Hence, sparse transverse TTs were sufficient as electrical conduits for rapid activation of Ca2+ release through ATs. Nanoscopy of atrial tissue sections confirmed abundant ATs as the major network component of AMs, particularly in human atrial tissue sections. Conclusions: AT junctions represent a conserved, cell-specific membrane structure for rapid excitation-contraction coupling throughout a representative spectrum of species including human. Since ATs provide the major excitable membrane network component in AMs, a new model of atrial “super-hub” Ca2+ signaling may apply across biomedically relevant species, opening avenues for future investigations about atrial disease mechanisms and their therapeutic targeting.
Im Titel ist "2+" hochgestellt
Gesehen am 30.07.2019